SYNTHESIS, CHARACTERIZATION, AND ANTIMICROBIAL EVALUATION OF 3,5-DISUBSTITUTED TRIAZOLES BEARING 5-CHLORO-2-METHYLINDOLE: SYNTHESIS OF NOVEL 1,2,4- TRIAZOLES - SABA SHIREEN; BHARATH RATHNA KUMAR P (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: Synthesis, characterization, and antimicrobial evaluation of some novel 1,2,4-triazole derivatives clubbed with indole. Methods: Procedure includes the synthesis of 1,2,4-triazole compounds by condensation reaction with ammonia. The synthesis was carried out in three steps with chlorophenylhydrazine hydrochloride as starting material with ethyl acetoacetate and hydrazine hydrate in the presence of ethanol to form hydrazide derivative. The hydrazide derivative then refluxed with ammonium acetate to get the desired compounds. Results: All the synthesized compounds were characterized and confirmed by Fourier-transform infrared spectroscopy, mass spectroscopy, and nuclear magnetic resonance spectroscopy. The new compounds (Va-f) synthesized were evaluated for antimicrobial activity. Conclusion: All the compounds Va-f screened for antimicrobial activity against selected strains of microorganisms. Compound Vb was found to be potent against Escherichia coli, Vc was found to be more active against Aspergillus niger.